Waterjet submucosal dissection of porcine esophagus with the HybridKnife and ERBEJET 2 system: a pilot study - Akutsu, Daisuke; Suzuki, Hideo; Narasaka, Toshiaki; Terasaki, Masahiko; Kaneko, Tsuyoshi; Matsui, Hirofumi; Mizokami, Yuji; Hyodo, Ichinosuke (Endoscopy International Open, 2017)
Background and study aims Esophageal endoscopic submucosal dissection (ESD) is technically difficult because of narrow working spaces and ease of perforation due to the lack of serosa. HybridKnife is a recently developed ESD device that is combined with the high pressure waterjet ERBEJET 2 system to lift mucosa. We hypothesized that this waterjet could make submucosal dissection safer and studied this in porcine esophagus.Materials and methods Water pressures of 30 – 70 bar were tested to determine the appropriate pressure for waterjet ESD with HybridKnife (WJ-ESD) in one pig. WJ-ESD safety and completion were compared with those of conventional ESD using DualKnife (C-ESD) as a reference. Each of three virtual esophageal lesions in two pigs were resected alternatively using both methods from the lower to upper esophagus. For WJ-ESD, the submucosa, apart from hard fibrous tissues, was dissected using water pressure alone.Results Using 50 bar of water pressure resulted in the best balance between proper dissection and view-disturbing water backflow. The dissection speeds for the lower, middle, and upper esophagus were 0.2, 0.9, and 0.2 cm2/min in 50 bar WJ-ESD and 1.1, 0.5, and 1.0 cm2/min in C-ESD, respectively. Minor bleeding was frequent in WJ-ESD, but was easily stopped by electrocoagulation with the same needle. No perforation was observed in either procedure. Thermal damage to dissected tissues appeared mild, and the extent of muscle injury was lower for WJ-ESD (4, 6, and 8 %) compared with C-ESD (14, 16, and 7 %).Conclusions WJ-ESD could be completed safely for porcine esophagus with less damage to the muscle layer compared with C-ESD.